Structure of public health consortiums: a study in the intermunicipal consortiums of health in the mata mineira area (Research, Society and Development, 2020)
One of the ways for small cities to deal rationally with the problems pointed out above has been through the municipalities associations for the implementation of public policies. Initiative is already foreseen in the legislation (law 11.107/95) and in the Federal Constitution itself of 1988 through the called intermunicipal consortia.  The purpose of intermunicipal health consortia is to make municipalities perform more efficiently and effectively the services vital to their population, based on the SUS principles. The municipalities come together to solve problems inherent to their region. Based on this vision, the intermunicipal health consortia seek to reduce costs and streamline accessible resources in order to offer medical assistance available in a municipality of the region to other municipalities in need of such services.  This research sought to verify how consortia are structured in terms of hierarchy, division of labor and sharing responsibilities. Interviews were carried out with the executive secretaries of the eight inter-municipal health consortia of Mata Mineira Area. For the analysis of the qualitative data was used the content analysis. For this, some subcategories were identified which are: physical structure, direction of the consortium, form of decision and apportionment. The results showed that they need improvements and adjustments so that they can successfully meet the objectives for which they were created.